2022
DOI: 10.1002/jev2.12226
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition influences fibroblast phenotype in colorectal cancer by altering miR‐200 levels in extracellular vesicles

Abstract: Colorectal cancer (CRC) with a mesenchymal gene expression signature has the greatest propensity for distant metastasis and is characterised by the accumulation of cancer‐associated fibroblasts in the stroma. We investigated whether the epithelial to mesenchymal transition status of CRC cells influences fibroblast phenotype, with a focus on the transfer of extracellular vesicles (EVs), as a controlled means of cell–cell communication. Epithelial CRC EVs suppressed TGF‐β‐driven myofibroblast differentiation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 91 publications
(123 reference statements)
1
16
0
Order By: Relevance
“…2G). In keeping with the mechanism described by Bhome et al (5), ZEB1 and ZEB2 (inducers of EMT; ZEB2 not shown), Vimentin (Vim), Cadherin 11 (CHD11) and a-SMA (ACTA2) were preferentially expressed in a small subset of cancer cell transcriptomes from patients de ned as having an active EMT1-EMT2-Epi expression program (Fig. 2H).…”
Section: Cancer Cell Emt Signatures Associate With the Fibroblasthigh...supporting
confidence: 84%
See 1 more Smart Citation
“…2G). In keeping with the mechanism described by Bhome et al (5), ZEB1 and ZEB2 (inducers of EMT; ZEB2 not shown), Vimentin (Vim), Cadherin 11 (CHD11) and a-SMA (ACTA2) were preferentially expressed in a small subset of cancer cell transcriptomes from patients de ned as having an active EMT1-EMT2-Epi expression program (Fig. 2H).…”
Section: Cancer Cell Emt Signatures Associate With the Fibroblasthigh...supporting
confidence: 84%
“…We have shown that the tumor-promoting and chemoprotective properties of CAFs are associated with an activated myo broblast (a-Smooth Muscle Actin/ACTA2 + ) phenotype that can be reversed with Phosphodiesterase type 5 inhibitors (PDE5i) (4). Recently, our colleagues provided a new mechanism for generating broblast heterogeneity, via the differential extracellular-vesicle (EV) transfer of miRNA, dependent on the epithelial or mesenchymal phenotype of the cancer, where mesenchymal colorectal cancer EVs (depleted for miR-200) did not suppress TGF-b-driven myo broblast differentiation (5). The actin cytoskeleton promotes myo broblast function during brogenesis and in tumor stroma remodeling (6).…”
Section: Introductionmentioning
confidence: 99%
“… [ 181 ] miR-200 family Colorectal cancer CRC cells with an epithelial phenotype but not a mesenchymal phenotype secrete miR-200 family members via EVs to attenuate TGF-β-mediated CAF features by targeting ZEB1 in normal fibroblasts. [ 45 ] miR-4534 Colorectal cancer Suppress autophagy to induce CAF phenotypes in fibroblasts. EV miR-4534 targets ATG2B expression.…”
Section: Cancer-derived Evs Can Dictate Preferable Caf Characteristic...mentioning
confidence: 99%
“…Given that aberrant p53 function can confer a CAF phenotype on fibroblasts [ 38 , 39 , 44 ], the expression status of the TP53 gene in both cancer cells and CAFs may reflect the features of CAF subtypes. Recently, Bhome et al demonstrated that the EMT phenotype of colorectal cancer (CRC) cells influences CAF generation [ 45 ] CRC cells with an epithelial phenotype secrete miR-200 family members via EVs to attenuate TGF-β-mediated CAF features by targeting ZEB1 in normal fibroblasts. However, EVs derived from CRC cells with a mesenchymal phenotype contain less miR-200 family, thus allowing TGF-β-mediated CAF feature induction.…”
Section: Cancer-derived Evs Can Dictate Preferable Caf Characteristic...mentioning
confidence: 99%
“…The EVs derived from tumor cells contribute to the formation of cancer-associated fibroblasts, inducing the remodeling of tumor stroma via transfer of pro-metastatic factors such as non-coding oncogenic micro ribonucleic acids (miRNAs) [ 37 ]. EV-mediated transferring of miR-200 from metastatic colorectal cancer cells to recipient fibroblasts promotes myofibroblast differentiation and fibronectin expression, shaping the stromal landscape, which is likely to be independent of local TGF-β availability [ 21 ]. EVs from SW620 colorectal cancer cells activate fibroblasts to invade the ECM through upregulation of pro-invasive regulators of membrane protrusion (PDLIM1, MYO1B) and matrix-remodeling proteins (MMP11, EMMPRIN, ADAM10) [ 22 ].…”
Section: Development Of Tumor Microenvironment By Evsmentioning
confidence: 99%